Effects of nitrogen and sulfur atom regulation on electrochemical properties of Na3V2(PO4)2F3 cathode material for Na-ion batteries. Issue 24 (15th December 2022) - Zhang, Xuntao; Tian, Hualing; Cai, Yanjun; Wang, Lei; Yao, Xiang; Su, Zhi
Abstract: The cathode material Na3 V2 (PO4 )2 F3 of sodium-ion battery is well-known for its large number of ion migration channels and high working voltage. However, the electrochemical performance of Na3 V2 (PO4 )2 F3 is not very outstanding. Thus, in the present study, Na3 V2 (PO4 )2 F3 cathode materials were successfully synthesized by using the sol-gel method and mechanical milling method to enhance the electrochemical performance. The physicochemical properties of synthesized Na3 V2 (PO4 )2 F3 were investigated by using X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, transition electron microscopy. X-ray diffraction spectroscopy indicates that the doping of nitrogen and sulfur did not alter the crystal form of Na3 V2 (PO4 )2 F3 . Transition electron microscopy image shows that Na3 V2 (PO4 )2 F3 has a thin carbon layer, and x-ray photoelectron spectroscopy illustrates the successful doping of nitrogen and sulfur into the carbon layer. The cyclic voltammetry curves show that the nitrogen and sulfur co-doped Na3 V2 (PO4 )2 F3 samples have good reversibility and low polarization. Materials with 15% thiourea has a high discharge specific capacity (126.9 mA h g −1 at 0.2 C) at the first cycle and excellent cycle stability (126.3 mA h g −1 after 100 cycles, a capacity retention of 99.5%) among the synthesized cathode materials. In the present study, the electrochemical performance of the Na3 V2 (PO4 )2 F3 cathode material was enhanced by regulation of co-doping of nitrogen and sulfur atoms.